Competitive Advantage and Service Marketing Mix - Didit Darmawan; Elodie Grenier (metromedia.education, 2021)
The marketing mix is one of the most important aspects of marketing activities and plays an important role in creating value and satisfaction to meet customer expectations. The concept of the marketing mix serves as a tool used by an organization to survive in a competitive environment. This concept is controlled by the organization and consists of four main components namely product, price, distribution and promotion. For bids in the form of services, the marketing mix develops into seven components according to the characteristics of the service offer. Three additional components are the service provider, process, physical evidence. The service marketing mix is a formulation of a competitive advantage strategy for organizations. The human factor directly involved in the exchange process makes human resources an important figure of strategic application. Customer-oriented competitive advantage should be implemented by service providers with the appropriate formulation of the marketing mix. Marketing mix and competitive advantage are strategic relationships that are very important for the survival of the company.